RANCANG BANGUN i-CRM (INTERACTIVE CUSTOMER RELATIONSHIP MANAGEMENT) UNTUK JASA AGEN PERJALANAN WISATA (Studi Kasus: PT Persada Duta Beliton) - Irvan Prastya; Sarip Hidayatuloh; Nidaul Hasanati (STUDIA INFORMATIKA: JURNAL SISTEM INFORMASI, 2017)
PT Persada Duta Beliton was established in 1989 in Tanjung Pandan city. The company made the first attempt to sell the airline ticket business, sailing vessel and hotel voucher. The services available at the company are currently less personally focused on customers. This resulted in the company not getting a more optimal valueand less on target. Therefore a business strategy is needed to optimize marketing, sales and service. Based on the research, the company currently does not have a media campaign that directly targeted to its customers and the absence of information storage media in the form of reviews from customers who have booked a tour package to assess the company's performance in order to improve the service is expected also able to provide more services in facilitating customers in interacting with company. The purpose of this research is to design an i-CRM information system at PT Persada Duta Beliton based website that can be used to maintain the company's relationship with the customer. The results to be achieved so that the system can have the function of booking tour packages, chat feature for customers to interact directly to the company in the system, the tour package reviews from customers and the existence of direct promotional media leads to customers as well as personalization to customers such as anniversary remarks include special discounts to customers. Model for system development is Rapid Application System (RAD). In system design is done by using tools Unified Model Language (UML).